Development of a genotyping platform for SARS-CoV-2 variants using high-resolution melting analysis. Issue 9 (September 2021) - Aoki, Akira; Mori, Yoko; Okamoto, Yoshinori; Jinno, Hideto
Abstract: Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus causing coronavirus disease 2019 (COVID-19), has been expanding globally since late 2019. SARS-CoV-2, an RNA virus, has a genome sequence that can easily undergo mutation. Several mutated SARS-CoV-2 strains, including those with higher infectivity than others, have been reported. To reduce SARS-CoV-2 transmission, it is crucial to trace its infection sources. Here, we developed a simple, easy-to-use genotyping method to identify SARS-CoV-2 variants using a high-resolution melting (HRM) analysis. Methods: We investigated five mutation sites, A23403G, G25563T, G26144T, T28144C, and G28882A, which are known strain determinants according to GISAID clades (L, S, V, G, GH, and GR). Results: We first employed synthetic DNA fragments containing the five characteristic sites for HRM analysis. All sequences clearly differentiated wild-type from mutant viruses. We then confirmed that RNA fragments were suitable for HRM analysis following reverse transcription. Human saliva did not negatively affect the HRM analysis, which supports the absence of a matrix effect. Conclusions: Our results indicate that this HRM-based genotyping method can identify SARS-CoV-2 variants. This novel assay platform potentially paves the way for accurate and rapid identification of SARS-CoV-2 infection sources.